The Role of Parents and Their Assessments in Encouraging Aspects of the Development of Early Children - Sanja Živanović; Ranka Perućica; Bojana Vuković; Slađana Ćalasan; Bojana Mastilo (Društvene i Humanističke Studije)
The family is the primary human community in which each individual creates his first experiences, the first agent of socialization that has a significant role in forming and encouraging a holistic network of aspects of child development. The aim of this research was to examine parents’ assessments of encouraging aspects of their children’s development. The sample consists of 79 parents of children aged three to six years and has the characteristics of a deliberate and opportunistic sample. The paper used the method of theoretical analysis and the method of empirical non-experimental research, and the techniques used were surveying and scaling. The results show that there are statistically significant differences in assessments of the encouragement of various aspects of child development depending on the gender of the parents, employment of the parents, vocational training of the fathers, parenting style, as well as the self-report of the family in which the parent grew up. Differences were not registered when it comes to the variables of parents’ age and mother’s education. Pedagogical implications are reflected in the indication of socio-demographic characteristics that can influence the stimulation of children’s development, in recommendations and guidelines for the actors of educational practice who work on cooperation with parents, and the advisory contribution from the pedagogical aspect in terms of family stimulation for quality child development.